2017
DOI: 10.1515/cclm-2016-0505
|View full text |Cite
|
Sign up to set email alerts
|

Can non-cholesterol sterols and lipoprotein subclasses distribution predict different patterns of cholesterol metabolism and statin therapy response?

Abstract: The results suggest the existence of different lipoprotein abnormalities according to various patterns of cholesterol homeostasis. Desmosterol/β-sitosterol ratio could be used for estimating individual propensity toward dyslipidemia development and direct the future treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
0
15
0
6
Order By: Relevance
“…However, in another study, common carotid artery intima-media thickness (CCA-IMT) correlated with serum cholesterol and sterol markers of cholesterol synthesis, but was weakly negatively correlated with the cholesterol absorption markers [12]. Furthermore, patients with cardiovascular disease had elevated markers of synthesis and decreased markers of intestinal cholesterol absorption in relation to controls, but also were older and had greater body mass index (BMI) [8]. Consequently, the controversy over the role in CVD of the synthesis and absorption markers of cholesterol remains.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in another study, common carotid artery intima-media thickness (CCA-IMT) correlated with serum cholesterol and sterol markers of cholesterol synthesis, but was weakly negatively correlated with the cholesterol absorption markers [12]. Furthermore, patients with cardiovascular disease had elevated markers of synthesis and decreased markers of intestinal cholesterol absorption in relation to controls, but also were older and had greater body mass index (BMI) [8]. Consequently, the controversy over the role in CVD of the synthesis and absorption markers of cholesterol remains.…”
Section: Introductionmentioning
confidence: 97%
“…Plasma non-cholesterol synthesis and absorption sterols have been utilized as markers of cardiovascular disease (CVD) [1][2][3][4][5][6]. Accordingly, compared with controls, established cardiovascular disease cases, not on lipid lowering medication, presented plasma sterols significantly higher as cholesterol absorption markers and lower as cholesterol synthesis markers [3,4,[6][7][8][9]. A review on the subject [10] suggested that in most of the studies increased level of the markers of cholesterol absorption is a risk factor for coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…Body cholesterol pool is maintained by delicate balance between the processes of cholesterol synthesis, absorption, and biliary secretion, all of which can be affected even by subtle alterations in thyroid hormones levels (60). Plasma noncholesterol sterols, including cholesterol precursors and plant sterols, are validated biomarkers of cholesterol biosynthesis and intestinal absorption efficiency (66). The results of a small study by Matysik et al (67) suggested that the levels of plasma non-cholesterol sterols could serve as indicators of disrupted cholesterol homeostasis in patients with hyper-and hypothyroidism.…”
Section: Hashimoto Thyroiditis and Dyslipidemiamentioning
confidence: 99%
“…Studies have shown inconsistent lipoprotein abnormalities across different patterns of cholesterol homeostasis. The 24-dehydrocholesterol/sitosterol ratio can be used to assess patient dyslipidemia and to guide treatment after disease progression [ 2 ]. A study showed that abnormal concentrations of low synthetic and high absorption markers of cholesterol in the blood reflect an impaired homeostatic environment, which is an important independent prognostic factor for the prevalence of cardiovascular disease in the population.…”
Section: Introductionmentioning
confidence: 99%